Integration of Local Wisdom in RBL-STEM Cascara Briquette Material to Improve Student Learning Outcomes - Komaria, N; Gita, R.S.D (Journal on Education, 2025)
Local wisdom represents cultural heritage with immense potential for contextualized and meaningful education. This study integration of local wisdom in the RBL-STEM cascara briquette material to improve student learning outcomes. The research utilized a quasi-experimental design involving high school students to evaluate the model's effectiveness. Instruments such as syllabus validation sheets, learning implementation plans, and achievement tests were validated with an average score of 92.4% (Very Valid). Results showed significant improvements in cognitive learning outcomes, with a normalized gain of 0.49 (Medium category) and a post-test average of 78.3. Teachers and students responded positively to the model, with average satisfaction rates of 88% and 78.8%, respectively. Challenges included limited implementation time and the need for teacher training on local wisdom integration. Overall, this study highlights the potential of RBL with local wisdom in enhancing critical thinking, cultural appreciation, and sustainable education. Future research should address scalability and long-term impacts.